Central Asia's Economy: Mapping Future Prospects to 2015 - Malcolm Dowling; Ganeshan Wignaraja (Asian Development Bank (ADB), 2006)
The growth performance of small, land-locked Central Asian economies has been among the world's fastest since the 1990s due to high-priced commodities (including oil and natural gas), strategic location, reasonable infrastructure, and human capital. The short-term economic prospects of Central Asian economies appear bright but long-term prospects may be less certain with a growing divergence between oil exporters (Azerbaijan, Kazakhstan, and Turkmenistan) and non-oil exporters (Kyrgyz Republic, Tajikistan, and Uzbekistan). This paper reviews their recent economic performance, projects key economic variables to 2015 against a constant global background, and discusses policy implications. Exploring various scenarios ("business as usual", "closing the gap" and "falling behind"), the paper highlights the importance of policies in determining the future development path of the Central Asian economies. The findings show that if these economies embrace policy reform, regional cooperation, and industrial competitiveness, then economic prosperity will continue to be enhanced.
hdl:11540/1877
Keywords: 330; Wirtschaftswachstum; Mineralölwirtschaft; Außenhandel; Wirtschaftslage; Zentralasien